Let
f ′ = 2 f 2 g h + g h 1 , f ( 0 ) = 1
g ′ = f g 2 h + f h 4 , g ( 0 ) = 1
h ′ = 3 f g h 2 + f g 1 , h ( 0 ) = 1 .
Find f ( 1 2 π ) + g ( 4 π ) + h ( 6 π ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
So darn close on this nonlinear ODE system.....I kept coming up with h(pi/6) = -1 for a grand total of 1 instead. Really good problem nonetheless, Rocco.....hope to see another similar ODE system like this?!
Very nice problem.
Problem Loading...
Note Loading...
Set Loading...
( 1 ) g h ∗ ( f ′ = 2 f 2 g h + g h 1 )
( 2 ) f h ∗ ( g ′ = f g 2 h + f h 4 )
( 3 ) f g ∗ ( h ′ = 3 f g h 2 + f g 1 )
( f g h ) ′ = f ( g h ) ′ + ( g h ) f ′ = f ( g h ′ + h g ′ ) + f ′ g h = f ′ g h + f g ′ h + f g h ′ ⟹
( f g h ) ′ = 6 ( ( f g h ) 2 + 1 )
Let y = f g h ⟹ y ′ = 6 ( y 2 + 1 ) ⟹ ∫ y 2 + 1 y ′ d y = 6 ∫ d x
⟹ arctan ( y ) = 6 x + C and f ( 0 ) g ( 0 ) h ( 0 ) = 1 = tan ( C ) ⟹ C = 4 π ⟹
f g h = tan ( 6 x + 4 π )
Dividing ( 1 ) by f ⟹ f f ′ = 2 f g h + f g h 1 = 2 tan ( 6 x + 4 π ) + cot ( 6 x + 4 π )
⟹ ln ( f ) = 6 2 ∫ tan ( 6 x + 4 π ) + 6 1 ∫ cot ( 6 x + 4 π ) + C ∗ =
ln ( K ( cos 2 ( 6 x + 4 π ) sin ( 6 x + 4 π ) ) 6 1 ) ⟹
f ( x ) = K ( cos 2 ( 6 x + 4 π ) sin ( 6 x + 4 π ) ) 6 1
f ( 0 ) = 1 ⟹ 1 = K ( 2 ) 6 1 ⟹ K = ( 2 1 ) 6 1
f ( x ) = ( 2 1 ( cos 2 ( 6 x + 4 π ) sin ( 6 x + 4 π ) ) ) 6 1 and f ( 1 2 π ) = 1
Similarly for g ( x ) and h ( x ) :
Dividing ( 2 ) by g ⟹ g g ′ = f g h + f g h 4 = tan ( 6 x + 4 π ) + 4 cot ( 6 x + 4 π ) ⟹
g ( x ) = K ( cos ( 6 x + 4 π ) sin 4 ( 6 x + 4 π ) ) 6 1
and g ( 0 ) = 1 ⟹ K = ( 2 2 3 ) 6 1 ⟹
g ( x ) = ( 2 2 3 ( cos ( 6 x + 4 π ) sin 4 ( 6 x + 4 π ) ) ) 6 1 and g ( 4 π ) = 1
Dividing ( 3 ) by h ⟹ h h ′ = 3 f g h + f g h 1 = 3 tan ( 6 x + 4 π ) + cot ( 6 x + 4 π ) ⟹
h ( x ) = K ( cos 3 ( 6 x + 4 π ) sin ( 6 x + 4 π ) ) 6 1
and h ( 0 ) = 1 ⟹ K = ( 2 1 ) 6 1 ⟹
h ( x ) = ( 2 1 ( cos 3 ( 6 x + 4 π ) sin ( 6 x + 4 π ) ) ) 6 1 and h ( 6 π ) = 1
⟹ f ( 1 2 π ) + g ( 4 π ) + h ( 6 π ) = 3